The theoretical framework of health beliefs on the stage of behavioral adoption of breast self-examination and mammography screening - Che Mohamed, Norfariha; Soo Foon, Moey (Kuliyyah of Allied Health Sciences, International Islamic University Malaysia, 2021)
Background: Breast cancer is one of the leading causes of cancer death amongst women and survival rates could be improved with early detection and access to optimal treatment. However, in Malaysia breast screening facilities were still underutilized. This study aimed to review behavior change theories that are applicable in formulating a theoretical framework to help design more effective interventions in promoting breast self-examination (BSE) and mammography screening amongst Malaysian women. Methods: Several electronic databases were searched for existing theories or models of behavior change associated with breast cancer screening. The relevant theories found included the health belief model (HBM), the theory of planned behavior (TPB), the trans-theoretical model (TTM), the theory of care seeking behavior (TCSB), the protection motivation theory (PMT) and the social cognitive theory (SCT). The theories were then reviewed for the appropriateness of constructs as well as for interrelated concepts in understanding the behavior of women to participate in breast cancer screening practices. The constructs in each theory were traced to its synonymy and points of overlap before integrating those theories. Result: Analysis of the theories indicated that they have the potential to improve understanding of the stage of behavioral change to adopt BSE and mammography screening amongst women. Thus, a theoretical framework integrating the theories has been developed to garner more operative ways to influence and change women’s behavior by studying the correlations between constructs in the framework. Conclusion: As there is evidence of the effectiveness of developing interventions based on social and behavioral science theories, it is then expected that this theoretical framework could help future researchers in preparing intervention programs towards enhancement of breast cancer screening behavior.